The Early Letters of Bishop Richard Hurd, 1739 to 1762. - Brewer, Sarah (Woodbridge : Boydell & Brewer, 1995)
A model edition of the early correspondence of one of George III's favourite bishops. ARCHIVES.
Frontmatter -- CONTENTS -- ACKNOWLEDGMENTS -- LIST OF CUE-TITLES AND ABBREVIATIONS -- BIOGRAPHY OF RICHARD HURD (1720-1808) -- BIOGRAPHIES OF CORRESPONDENTS -- THE CORRESPONDENCE -- LIST OF LETTERS -- THE TEXT -- EDITORIAL PRINCIPLES -- THE LETTERS.part 1 -- THE LETTERS.part 2 -- APPENDIX -- BIBLIOGRAPHICAL LIST OF HURD'S WORKS -- BIBLIOGRAPHY -- INDEX
Print version record.
JSTOR
Keywords: Hurd, Richard, -- 1720-1808 -- Correspondence; Church of England -- Clergy -- Correspondence; Church of England -- Clergé -- Correspondance; Hurd, Richard, -- 1720-1808; Church of England; Authors, English -- 18th century -- Correspondence; England -- Intellectual life -- 18th century; Écrivains anglais -- 18e siècle -- Correspondance; Angleterre -- Vie intellectuelle -- 18e siècle.; LITERARY CRITICISM / General; Authors, English; Clergy; Intellectual life; England; 1700-1799; Personal correspondence